2018
DOI: 10.6018/turismo.41.327051
|View full text |Cite
|
Sign up to set email alerts
|

Turismo y economía colaborativa: El caso de los recorridos gratuitos a pie en Barcelona

Abstract: <p>El turismo ha sufrido un profundo cambio estrechamente vinculado con el acelerado uso del Internet y las redes. En este marco, el concepto de visitas guiadas gratuitas, sin cargo alguno se está haciendo cada vez más popular en toda Europa. El presente artículo analiza desde un enfoque exploratorio y partiendo de los principios de la geografía económica evolutiva, las empresas de recorridos gratuitos a pie en el marco de la economía colaborativa en Barcelona. Este enfoque permite entender este emergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…The literature indicates a growing consensus that wine tourism tends to be a sustainable growth model capable of boosting Wine tourism's increasing popularity can be explained by two factors, namely, the greater availability of leisure time and a growing appreciation of local gastronomic features (Medina, Serrano & Tresserras, 2011). Researchers such as Boniface (2003) and Leal (2013) have suggested that gastronomic tourism is an expression of post-modern societies and a reaction to industrialisation and McDonaldisation as this sector appeals to those who value local, traditional and authentic experiences lived through agri-food products. In this vein, the UNWTO and the Basque Culinary Center (2019) report that a new type of tourist has emerged whose primary motivation is getting to know and enjoying their destination's culinary culture.…”
Section: Development Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature indicates a growing consensus that wine tourism tends to be a sustainable growth model capable of boosting Wine tourism's increasing popularity can be explained by two factors, namely, the greater availability of leisure time and a growing appreciation of local gastronomic features (Medina, Serrano & Tresserras, 2011). Researchers such as Boniface (2003) and Leal (2013) have suggested that gastronomic tourism is an expression of post-modern societies and a reaction to industrialisation and McDonaldisation as this sector appeals to those who value local, traditional and authentic experiences lived through agri-food products. In this vein, the UNWTO and the Basque Culinary Center (2019) report that a new type of tourist has emerged whose primary motivation is getting to know and enjoying their destination's culinary culture.…”
Section: Development Strategiesmentioning
confidence: 99%
“…Wine and food tourism's positive effect on local development has attracted the attention of academia, destination-marketing policymakers and strategists (Leal, 2013). European countries, in particular, have made an especially intensive effort to promote wine products through wine tourism by creating the European Network of Wine Cities (De Jesús-Contreras, Thomé-Ortiz & Medina, 2020).…”
Section: Development Strategiesmentioning
confidence: 99%
“…These new ways of operating clash with the inertias of the tour guide sector, on the whole organised in professional associations which negotiate and contact the tourism administration of the destination (del Pilar Leal Londoño and Medina, 2018; Meged and Zillinger, 2018; Navalón-García and Mínguez, 2016). To date, the administration-guide-user relationship has worked in a coordinated way based on collaboration patterns and mutual recognition.…”
Section: Regarding the Free Tours Phenomenonmentioning
confidence: 99%
“…They focus their studies on the relationships between (1) Guide’s relationship with the places they visit and their communities; (2) Its interaction with other activities and with tour operators; (3) Their interaction with consumers; (4) The incorporation of technology and (5) Its orientation to market niches. But the relationship of the tourist guide with the new formulae of collaborative economy and with the free tours are still scarce (Bryon, 2012; del Pilar Leal Londoño and Medina, 2018; Meged and Zillinger, 2018; Navalón-García and Mínguez, 2016; Zillinger et al, 2012). This opens a new field of research that must be addressed since this growing practice highlights some considerably important issues.…”
Section: Introductionmentioning
confidence: 99%
“…Academic interest in free guided tours has focussed on large cities where cultural tourism is predominant and where the impact has been greatest, such as Berlin (Nilsson & Zillinger, 2020), Amsterdam (de Waal & Arets, 2022; Koerts, 2017) and Barcelona (Leal Londoño & Font Medina, 2018; Viana-Lora & Nel-lo-Andreu, 2023). As in some of the major cities where short-term holiday rentals have spread uncontrollably, cultural destinations are witnessing a greater proliferation of free tours (García & Ruiz, 2022).…”
Section: Introductionmentioning
confidence: 99%